2009
DOI: 10.1002/esp.1783
|View full text |Cite
|
Sign up to set email alerts
|

The spatial and temporal patterns of aggradation in a temperate, upland, gravel‐bed river

Abstract: Intensive field monitoring of a reach of upland gravel-bed river illustrates the temporal and spatial variability of in-channel sedimentation. Over the six-year monitoring period, the mean bed level in the channel has risen by 0·17 m with a maximum bed level rise of 0·5 m noted at one location over a five month winter period. These rapid levels of aggradation have a profound impact on the number and duration of overbank flows with flood frequency increasing on average 2·6 times and overbank flow time increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…Cross-sections were used for quantifying volumes of erosion and deposition in the channel and back-calculating bedmaterial sediment transport using the morphological method (Ashmore and Church, 1998), widely applied for balancing sediment budgets in gravel-bed rivers (Ferguson and Ashworth, 1992;Martin and Church, 1995;Raven et al, 2009;Reid et al, 2007). Volumes of deposition (V D ) and erosion (V E ) between cross-sections are obtained by the following:…”
Section: Channel Storage Changesmentioning
confidence: 99%
“…Cross-sections were used for quantifying volumes of erosion and deposition in the channel and back-calculating bedmaterial sediment transport using the morphological method (Ashmore and Church, 1998), widely applied for balancing sediment budgets in gravel-bed rivers (Ferguson and Ashworth, 1992;Martin and Church, 1995;Raven et al, 2009;Reid et al, 2007). Volumes of deposition (V D ) and erosion (V E ) between cross-sections are obtained by the following:…”
Section: Channel Storage Changesmentioning
confidence: 99%
“…Such views clearly result from reliable observations and personal experience, and these opinions are common in the UK after floods (see, for example, Environment Agency, 2007). Importantly, other research in North Yorkshire has found that the aggradation of sediment in an upland river (the River Wharfe near Buckden; see Figure 1a) influences changes in flooding (Lane et al, 2007;Raven et al, 2009), and modelling based on participatory research in Pickering found that vegetation and sediment build-up around river channels can increase flood risk (Whatmore, Ward, and Lane, 2008). It is debatable whether recent reports of public frustration regarding the lack of river dredging and blaming of the Environment Agency after floods in England (Merrill, 2014;Smith, 2014) suggest a tendency to blame others in the face of flood risk (Harries, 2013) or reflect views of 'ignorant but arrogant experts' disregarding local knowledge and expertise (Wynne, 1992, p. 295).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this potential problem and maintain a progressive increase in flow with rising stage, it is prudent to further partition the cross-section when compositing discharge and investigate its impact. Inevitably, though, flow partitioning to generate a channel discharge (and thus specific stream power) over the active bed will be subject to uncertainties in selecting Manning n coefficients for the different flow areas in Equation (9).…”
Section: Channel Dischargementioning
confidence: 99%
“…Conversely, if sediment supply is greater than the transporting capacity, then sedimentation processes are more likely to predominate with potential for channel instability through aggradation and/or channel narrowing. Deposited sediment can be a critical factor in flooding [8][9][10], reducing in-channel conveyance and the standard of protection afforded by defences, resulting in maintenance problems [11,12]. Additional complex responses to channel instability include tributary rejuvenation through headcutting, accelerated rates of lateral mobility in meandering rivers [13,14] and channel widening as flow is deflected around maturing sediment bars, both of which could threaten linear flood defences not set back from the channel.…”
Section: Introductionmentioning
confidence: 99%